PENGARUH EFEKTIVITAS PENERAPAN SISTEM INFORMASI AKUNTANSI, BUDAYA ORGANISASI DAN KESESUAIAN TUGAS PADA KINERJA KARYAWAN - Veriana, Putu Ayu Agnes; Budiartha, I Ketut (E-Jurnal Akuntansi, 2016)
The purpose of this study is to determine the effectiveness of Accounting Information Systems (AIS), organizational culture and compliance duties on the performance of employees in the LPD in Mengwi. This research was conducted in the LPD in Mengwi. The population in this study are employees who use information technology. The samples in this study using probability sampling with simple random sampling technique is done on the LPD in Mengwi. Total sample obtained is 53 employees. This study used multiple linear regression analysis techniques. The results of this study show that the effectiveness of the implementation of the SIA, the organizational culture and suitability task positive influence on employee performance. This indicates that the higher the effectiveness of the implementation of the SIA, the organizational culture and the suitability of the task, the higher the performance of employees at LPD in Mengwi.
Keywords: Effectiveness SIA Implementation, Organizational Culture, Compliance Tasks, Employee Performance